Paths in Heidegger's Later Thought - Yang, Guang; Keiling, Tobias, 1983-; D'Angelo, Diego; Figal, Günter, 1949- (Book collections on Project MUSE., 2020)
"If one takes Heidegger at his word then his philosophy is about pursuing different "paths" of thought rather than defining a single set of truths. This volume gathers the work of an international group of scholars to present a range of ways in which Heidegger can be read and a diversity of styles in which his thought can be continued. Despite their many approaches to Heidegger, their hermeneutic orientation brings these scholars together. The essays span themes from the ontic to the ontological, from the specific to the speculative. While the volume does not aim to present a comprehensive interpretation of Heidegger's later thought, it covers much of the terrain of his later thinking and presents new directions for how Heidegger should and should not be read today. Scholars of Heidegger's later thought will find rich and original readings that expand considerations of Heidegger's entire oeuvre."-- Back cover.